Barganha legislativa, Lei de Gamson e justiça distributiva : uma análise quase-experimental sobre formação de coalizão - Bruno Rodrigues Pinheiro (2020)
This thesis consists of three articles on legislative bargaining and portfolio allocation in parliamentary democracies in a quasi-experimental perspective. In the first article,I analyze the relationship between the party size and the institutional centrality of investiture rules in the selection process of the formateur party. In the second, I discuss the existence of ministerial bonus in the portfolio allocation to the formateur party, comparing Gamson’s law with Baron and Ferejohn’s (1989) and Morelli (1999) legislative bargaining models. Finally, in the last article, I analyze the existence of the relative weakness effect in portfolio allocations and the long-term stability of coalitions, making Gamson’s propositions compatible with Rawls’s (1971) maximin rule of distributive justice, connecting delegation of power, resource sharing and fairness with the making and breaking of governments